Manifestações orais e laserterapia de baixa intensidade em pacientes com Síndrome de Sjögren em Cascavel/PR - Waligura, Lariana Rafaela Ribeiro (2024)
Sjögren's syndrome (SS) is a systemic autoimmune exocrinopathy. The etiology of this disease is unknown, and different predisposing factors and processes related to the immune system have been described in its etiopathogenesis, suggesting that this disease is multifactorial. It affects more in the fourth and fifth decades of life and a proportion of 9 women and 1 man. SS is a chronic inflammatory disease characterized by lymphocytic infiltration of the lacrimal and salivary glands, resulting in the following primary symptoms: xerophthalmia (dry eyes) and xerostomia (dry mouth). There are few published data on oral manifestations in patients with this pathology. The present study is a nonrandomized clinical study carried out in two phases. The first phase aimed to evaluate the oral manifestations present in patients diagnosed with SS who were identified in a previous study by our research group. Patients who agreed to participate in the study underwent oral clinical examinations to confirm the oral and systemic findings. In the second stage, patients who presented an abnormal salivary flow parameter, underwent laser therapy on the salivary glands to highlight the potential of laser as a treatment for this symptom. The frequencies of clinical variables (manifestations) were analyzed with emphasis on the clinical aspects of the disease, with the data are presented in the form of descriptive statistics and were analyzed using Microsoft Office Excel and XLSTAT software. The tests considered 5% significance. Among the 64 patients with SS, 11 patients were evaluated, all female, and the sensation of dry mouth was a present in 100% (n=11), following alterad taste, halitosis and use of acquired prosthesis in 54.45% (n=6). Of the patients evaluated, 45,55% (n=5) had dental caries and after treatment with laser therapy, the results of unstimulated sialometry were for normal flow salivation from 18,82% to 54,45%. However, in stimulated sialometry, in went from 27,73% to 36,64% after laser therapy. Thus, the present study demonstrated that the main clinical of manifestations of patients of SS is the sensation of dry mouth and that laser therapy can increase salivary flow in patients detected with hyposalivation.